Kur’an’ın engellilere yaklaşımı - Gül, Emine (My University, 2004)
Tarihi süreç içinde engelli insanlar toplumsal hayatta farklı muamelelere tabi tutulmuşlardır. İnsanların davranışlarına inancın etkisini kabul eden pek çok insan Kur'an'ın engellilere yaklaşımını öğrenmek istemektedir. Bu çalışmada, engelli insanların Kur'an'da yer alışı ve mü'minlerin engellilik durumunu kavrayışlarının nasıl olması gerektiği ayetlerle ortaya konmaktadır. Kur'an engellilerin yaşamlarında kolaylığı esas alarak sorumluluklarını engelleri oranında azaltmış ancak kulluk yükümlülüğünden muaf tutmamıştır. Kur'an'da bahsi geçen tüm engelli insanlar toplumsal ve dini alanlarda var olmuşlar ve Kur'an'da bunu teşvik etmektedir. Peygamberimiz, durumlarına göre engelli kişileri çalışmaya teşvik ederek onları kabiliyetlerine göre farklı birimlerde istihdam ederek, engellilerin ticaret yapmasını kolaylaştıracak hükümler koymuş ve zihinsel engelli kimselerin dini yükümlülüklerden muaf tutulduğunu belirtmiştir. Sağlıklı kimselerin engelli kimselerle bir arada yaşamaları konusunda temel ahlaki prensipleri açıklayarak bu hususa teşvikte bulunmuş ve görme engelliye yol göstermeyi, sağır ve dilsize laf anlatmayı da sadaka olarak değerlendirmiştir. Bir kimse başka kimselerin ve/ veya yakınlarının günahı mukabili bir ceza olarak engelli konuma getirilemez. Zira genel geçer kaideye göre kimse kimsenin günahını üstlenemez. Engellilik, herhangi bir hata, ihmal ve günahın olmadığı durumlarda da insana verilebilir ki bu da Allah'ın insanları imtihan etmesi gerçeğidir. Bu bağlamda olması gereken, imtihan olgusu iyi kavranarak; Allah'ın adâlet ve merhametinden şüphe etmeden, sabır ve dua ile en güzel sonuca ulaşmaktır. In the course of time, handicapped people have faced different treatments in their social life. Many people who believe in the fact that the faith has an impact on the human behavior are interested in knowing how the approaches of Koran to handicapped people in general. In this study, we will establish the disability matter the way it's addressed in the Koran and how the believers should comprehend the issue. To ease the life of the disabled people, Koran lessens the religious duties of the individual in accordance with the level of his/ her disability instead of totally freeing the duties. All handicapped people mentioned in the Koran have been part of the social and religious life one way or another. The prophet of Islam encouraged the disabled people for work. He also set rules for the accommodation of the disabled in the commercial life so that all individuals can participate in life in accordance with the ability level at hand. The prophet also indicated that only the mentally disabled people are excluded of the religious duties. The prophet's moral principles set the tone for the community so that all could learn how to live in harmony and in peace with no discrimination against any group including the disabled. In his value system, showing the way to the blind or translating some words to the deaf was equal to performing charity. Nobody can be caused to be handicapped because of the sins committed by his relatives or by any other person. The general Islamic rule dictates that each individual is solely responsible for his/ her own doings and the sins once committed may not be taken ownership by others. On the other hand, the condition of being handicapped can be the destiny of the person even though he/ she is known to be free of any error, sin or negligence. This case then is interpreted to be a lessonic case for the others to reflect upon or to learn from. In this situation, it is expected from the people that they should accept the destiny given by the All-Knowing, with patience and prayers, without questioning the justice or the mercy of The All-Mighty.
Keywords: İslam; Tefsir